LITERATURE REVIEW: ASUPAN ENERGI DAN PROTEIN DENGAN STATUS GIZI PADA BALITA - Ananda Putri Fadlillah; Novera Herdiani (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The problem of nutritional status of children under five is still a world concern, around 45% of under-five deaths are due to malnutrition. The nutritional status of toddlers is influenced by many factors, one of which is energy and protein intake. A prolonged lack of energy and protein intake can cause nutritional problems for toddlers, one of which is Protein Energy Deficiency (KEP). This literature review aims to determine energy and protein intake with nutritional status in toddlers. The method used is a traditional literature review, articles are collected using the Garuda Portal and Google Scholar databases with a span of 2016-2020. The search results obtained 321 articles on Garuda Portal and 4060 articles on Google Scholar about energy and protein intake with nutritional status in toddlers. There are 14 articles that are used as references in writing this literature review which shows that energy and protein intake is related to the nutritional status of children under five. Energy intake is useful for toddler activities and growth and is related to the nutritional status of children. Protein intake is useful for the formation of body immunity so that it is related to the nutritional status of children. The conclusion of this research is that sufficient energy and protein intake can support the growth and development and nutritional health of toddlers. Suggestions in this study for health workers are expected to provide education to parents of toddlers regarding the importance of nutritional intake and nutritional status of toddlers. Keywords: Energy, Protein, Nutritional Status of Toddler